Multisystem Tuberculosis: Importance of Clinical Signs, Neuroimaging and Drug Compliance - Sahil Bhandari; S. Balamurugan; Gajendra Kumar Verma; Hemal Kenia (Delhi Journal of Ophthalmology)
Tuberculosis, caused by Mycobacterium tuberculosis, primarily affects the pulmonary system and is characterized pathologically by caseating granulomas. Extrapulmonary systems can get involved primarily or secondarily. We report a subject who presented initially with subretinal abscess (intraocular tuberculosis) and papulonecrotic tuberculids (cutaneous tuberculosis). He responded well to medical treatment but discontinued it only to present with right sided pupil sparing complete third cranial nerve palsy (neuro-tuberculosis) and testicular hydrocele (genitourinary tuberculosis). Re-initiation of medical treatment completely resolved both. Significance of this case highlights the fact that four different extrapulmonary systems were involved in a single subject in continuum with no evidence of obvious pulmonary tuberculosis. It also shows the role of strict drug compliance which otherwise can lead to recurrences or secondary multi-system involvement.